2019
DOI: 10.1371/journal.pone.0215228
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with the occurrence of anthrax outbreaks in livestock in the country of Georgia: A case-control investigation 2013-2015

Abstract: Introduction Anthrax is considered endemic in livestock in Georgia. In 2007, the annual vaccination became the responsibility of livestock owners, while contracting of private veterinarians was not officially required. Six years later, due to increase in human outbreaks associated with livestock handling, there is a need to find out the risk factors of livestock anthrax in Georgia. Objective To identify exposures and risk factors associated with livestock anthrax. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…An interesting finding in our study was the 10-fold higher anthrax events in cattle when compared to other livestock, findings similar to those reported in Australia, Lesotho, Zambia, and Zimbabwe [ 36 40 ]. Whereas it is possible that this finding represents reporting bias in favor of cattle, it may not fully explain the high levels of cattle events reported since livestock anthrax reports are closely linked with human infections that drive the reporting.…”
Section: Discussionsupporting
confidence: 90%
“…An interesting finding in our study was the 10-fold higher anthrax events in cattle when compared to other livestock, findings similar to those reported in Australia, Lesotho, Zambia, and Zimbabwe [ 36 40 ]. Whereas it is possible that this finding represents reporting bias in favor of cattle, it may not fully explain the high levels of cattle events reported since livestock anthrax reports are closely linked with human infections that drive the reporting.…”
Section: Discussionsupporting
confidence: 90%
“…Most of the laboratory facilities are situated far away from the endemic area, making it difficult to transport the samples for analysis due to limited transport facilities in those areas 1 16 . Studies in Georgia has highlighted the importance of supervision during carcasses disposal, monitoring by service providers, training sessions for surveillance system strengthening and inter-sectoral coordination as key strategies to prevent anthrax 17 18 .…”
Section: Discussionmentioning
confidence: 99%
“…A greater proportion of controls reported knowing of animal anthrax deaths compared to human infections. Perhaps this experience motivated the controls to vaccinate their animals against anthrax, as a key finding from the primary case-control study found a statistically significant protective effect of anthrax vaccination within the previous two years [10].…”
Section: Discussionmentioning
confidence: 99%
“…Separate area controls were included to examine risk factors and exposures that could affect herd-level management practices to understand what some herds are doing differently that puts them at risk for the disease. These controls were outside the “intervention zone” that received anthrax control measures following the animal anthrax death [10], but were proximal to expect similar anthrax risk.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation